Abundance, distribution and breeding success of the endemic Gough Island Finch Rowettia goughensis between 2009 and 2018. (2nd July 2020) - Jones, Christopher W.; Risi, Michelle M.; Osborne, Alexis M.; Parker, Graham C.; Rexer-Huber, Kalinka; Le Bouard, Fabrice; Cleeland, Jaimie B.; Lawrence, Katrina; Kinchin-Smith, David; Witcutt, Emma; Starnes, Thomas; Bond, Alexander L.; et al.
ABSTRACT: The impacts of invasive house mice Mus musculus have received increasing attention on islands where mice are the only invasive rodent species. On Gough Island, the impact of mice on seabirds has increased over the past decade, but the current population status of the Critically Endangered Gough Finch Rowettia goughensis is uncertain. Based on nest monitoring at high elevation sites in 2009 ( n = 37) and 2018 ( n = 45), we found mean nest survival of 55% in both years and a fecundity of 1.31 ± 0.69 fledglings per pair in 2018. Density estimates from territory mapping in 2009 and 2018 were similar to past estimates and indicated little change in upland habitat. Density estimates from line transect distance sampling surveys around the island from 2018 to 2020 revealed higher densities in moorland (55.4 birds/km 2 ) and wet heath (29.5 birds/km 2 ) habitats, compared to coastal tussock (10.9 birds/km 2 ) and lowland fern bush habitat (2.6 birds/km 2 ). Extrapolating these habitat-specific densities across the island indicates a global population of Gough Finches in 2020 of 1917 individuals (95% CI: 1550–2500). Future population surveys using the same design could detect population changes of 40% or more. Our population estimate provides an important baseline for future monitoring following the planned eradication of house mice from Gough Island in 2021. However, we highlight that greater monitoring effort may be needed to increase the power to detect smaller population changes after an invasive species eradication.